“My supervisor is so busy…”. Informal spaces for postgraduate learning in the Health Sciences. - Grossman, E S (South African Journal of Higher Education, 2016)
This descriptive study investigates a one-on-one writing consultancy as an informal learning space, formed to assist postgraduate research students (PRS) with thesis writing. The consultancy was held monthly on Sundays and appointments booked for up to one hour. During that time writing problems were identified and recommendations made to overcome these. Over the nine months 52 consults were held with 23 PhDs and 21 Master’s candidates, the remaining consults were for non-degree writing purposes. Consults proved dichotomous with advice sought for both writing and non-writing related issues. Conspicuous were findings indicative of the high workloads carried by supervisory staff which thwarted PRS interaction. The one-on-one consultancy has many characteristics of alternative research-related spaces used elsewhere to provide PRS support. It is suggested that informal learning spaces, similar to the one-on-one writing consultancy, be investigated as a way to support PRSs and improve their throughput numbers.